Uterine Hyperplasia Causes, Symptoms Consequences and Principles of Treatment - Abdullo Akramov Axmad og‘li; Raxmatov Jasurbek Xurshid oʻgʻli; Uroqova Marjona Shamsiddin qizi; Isaqulov Ulug'bek Alisher o'g'li; Ibrohimova Shahnoza Ilhom qizi; Zairov Laziz Shuxratovich (Journal of Medical Genetics and Clinical Biology, 2024)
In this article, the causes, symptoms, consequences, and treatment principles of Uterine Hyperplasia are described in detail, as well as an example of research conducted by world scientists.